The Vocabulary Acquisition Though Nursery Rhymes by Al-Azhar Kindergarten Children - Ghulam Ikhwan Fhadilla; Otong Setiawan Djuharie; Deni Suswanto (Epigram, 2025)
This research examines English vocabulary acquisition among kindergarten students through nursery rhymes within the Indonesian educational context, integrating psycholinguistic theories including Chomsky's Universal Grammar, Krashen's Input Hypothesis, and Piaget's Cognitive Development Theory. The study addresses two primary questions: (1) What types of vocabulary are acquired by Al-Azhar Kindergarten children through nursery rhymes? (2) How are certain vocabulary types more frequently acquired through nursery rhymes? The research objectives are to identify and categorize vocabulary types acquired and indicate vocabulary acquisition patterns related to children's cognitive development stages. Employing a qualitative approach, this study observed 25 kindergarten students aged 5-7 years from Al-Azhar Syifa Budi Parahyangan Kindergarten, Padalarang, West Bandung, using purposive sampling. Data collection utilized observational protocols, video recordings, and post-test assessments conducted over four weeks, with each week introducing a different nursery rhyme: "Vegetable Song," "I'm Thirsty!" "Fruit Song," and "Open Shut Them." Songs were presented during daily circle time, with supplementary learning activities on Tuesdays and post-test evaluations on Fridays using flashcard-based verbal identification. Results demonstrate distinct acquisition patterns aligned with Piaget's Preoperational stage framework. Concrete nouns representing tangible objects (vegetables, fruits, beverages) and action verbs achieved significantly higher acquisition rates, compared to abstract adjectives which require more complex cognitive processing. Kinesthetic approaches, particularly in "Open Shut Them," proved exceptionally effective, achieving high mastery by pairing linguistic input with physical actions, thereby transforming abstract vocabulary into embodied learning experiences. The study concludes that nursery rhymes' melodic structure, rhythmic patterns, and repetitive nature provide comprehensible input at students' "i+1" level, facilitating subconscious language acquisition through multisensory engagement. Vocabulary development is significantly influenced by environmental exposure, experiential learning, instructional tempo, and developmental appropriateness. These findings validate music-based pedagogical strategies that leverage repetition, physical engagement, and contextual relevance for optimizing vocabulary retention among young English learners in Indonesian kindergarten contexts. Keywords: Vocabulary acquisition, Nursery Rhymes, Second language acquisition, Psycholinguistic